2016
DOI: 10.2147/jmdh.s95319
|View full text |Cite
|
Sign up to set email alerts
|

Improving perioperative care for adolescent idiopathic scoliosis patients: the impact of a multidisciplinary care approach

Abstract: The complex nature of the surgical treatment of adolescent idiopathic scoliosis (AIS) requires a wide variety of health care providers. A well-coordinated, multidisciplinary team approach to the care of these patients is essential for providing high-quality care. This review offers an up-to-date overview of the numerous interventions and safety measures for improving outcomes after AIS surgery throughout the perioperative phases of care. Reducing the risk of potentially devastating and costly complications aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 87 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…This expedited hemostasis reduces both blood loss as well as operative time, another potential factor in developing an SSI. 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This expedited hemostasis reduces both blood loss as well as operative time, another potential factor in developing an SSI. 5 …”
Section: Discussionmentioning
confidence: 99%
“…However, there is a growing consensus that the most effective means of reducing the risk of SSIs is a broad based, multidisciplinary approach. 4 - 6…”
Section: Introductionmentioning
confidence: 99%
“…Bellaire et al14 had a pre-ERAS average LOS of 4.9 reducing this further to 4 with an ERAS that included decreased time to the imitation of oral food and pain medication. The LOS in the Bellaire and colleagues study is already (before intervention) lower than the average in any other studies, illustrating this institution's dedication to rapid discharge as several other studies in other categories originate for the same institution 4,14,21…”
Section: Discussionmentioning
confidence: 70%
“…The LOS in the Bellaire and colleagues study is already (before intervention) lower than the average in any other studies, illustrating this institution's dedication to rapid discharge as several other studies in other categories originate for the same institution. 4,14,21 In 2015 Pearsall et al 22 examined barriers to the adoption of ERAS, here they identified the lack of education at all levels of the team involved in the patient's care as a major barrier. In our study, it could seem as adopting the general principle ideas of ERAS can have a large impact on other patient categories.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Hence, an MAP >65 mmHg during dissection and a higher pressure goal of 75 mmHg are recommended during correction. [28] In Group I, there was almost no demand for nitroglycerine. The favorable surgical field allowed higher MAP that permits better tissues’ perfusion.…”
Section: Discussionmentioning
confidence: 99%